Adherence to Mediterranean diet and risk of gastric cancer: results of a case–control study in Italy. Issue 6 (November 2017) - Stojanovic, Jovana; Giraldi, Luca; Arzani, Dario; Pastorino, Roberta; Biondi, Alberto; Persiani, Roberto; Boccia, Stefania; Leoncini, Emanuele
Abstract : The aim of this study is to evaluate the association between adherence to Mediterranean diet (MD) and gastric cancer (GC). A case–control study was carried out at the Fondazione Policlinico 'A. Gemelli' (Rome, Italy) from 2003 to 2015. A total of 223 incident cases and 223 controls were interviewed. Dietary intake was assessed through a validated food frequency questionnaire that collected information on more than 25 food items. The association between adherence to MD and risk of GC was quantified by calculating Odds Ratios (OR) and 95% confidence intervals (CI). The analysis reports that a higher adherence to MD is associated with a reduced risk of GC (OR: 0.70; 95% CI: 0.61–0.81). A high consumption of vegetables (OR: 0.34; 95% CI: 0.14–0.85), legumes (OR: 0.13; 95% CI: 0.06–0.29), and fish (OR: 0.33; 95% CI: 0.15–0.68), as well as low consumption of meat (OR: 0.29; 95% CI: 0.10–0.85) and alcohol (OR: 0.46; 95% CI: 0.24–0.90) are consistently related to a lower risk of GC. Our study indicates a protective role of the MD eating pattern and MD individual components against GC. Our results showed a beneficial role of high vegetable, legume, and fish consumption, along with low intake of alcohol and meat in the development of GC.